Development of physics learning modules in supporting the implementation of digitalization education wave material based on Augmented Reality (AR) and Physics Education Technology (PhET) - Handayani, Iryan Dwi; Zhafira, Talitha; Kusumaningrum, Yulinda (ORBITA: Jurnal Pendidikan dan Ilmu Fisika, 2024)
The era of the industrial revolution 4.0 and 5.0 is the era of digitalization, the era in which the man who drives the development of the country's economy has been slowly replaced by mechanical automation and digitization of technology. The role of science and technology is necessary for the success of the digitalized era of education. Technology-based modules are essential to digitizing education and avoiding loos learning. The technology that can be used to digitize education is using three-dimensional images using augmented reality technology integrated using PhET (Physic Education Technology). The research aims to implement Augmented Reality (AR) and Physics Education Technology (PhET) in the development of physical modules for enterprise materials and renewable energy. This module will be about materials and renewable energy which contains barcodes that when scanned using a student's smartphone, then will appear a real three-dimensional picture. While business practicums and renewable energy will emerge in the form of links that will later be connected to PhET and students can simulate experiments on energy change, enterprise and renewed energy. The research method uses the ADDIE development model, namely analysis, design, development, implementation and evaluation. The research was carried out at Kesatrian 2 Semarang High School involving 50 students and 2 specialists. PhET-based and Augmented Reality learning modules applied to the experimental class can help students to improve their problem-solving skills. an evaluation of the applications already implemented in the school, which assessed the effectiveness of the use of AR and PhET learning modules on vibrational and wave material. Effectiveness can be reviewed from the response of students who have used the reviewed module from the level of comprehension of the material. The effectiveness score reaches 83%, which means that the module is developed effectively to support the process of learning activities in the classroom.